Optimasi Proses Ekstraksi Oleoresin Jahe (Zingiber officinale Rosc) Menggunakan Ultrasonik - Hartuti, Sri; Supardan, Muhammad Dani (Jurnal Rekayasa Kimia & Lingkungan, 2012)
The study on extraction of oleoresin from ginger by using ultrasonic was carried out in order to obtain the optimum condition of extraction process. The effect of ratio of ginger to solvent (ethanol, X1), extraction temperature (X2), and extraction duration (X3) are studied on the yield of oleoresin. Response surface design method with Central Composite Design (CCD) was used to obtain a mathematical model which describes the relationship between the yield of ginger oleoresin and influencing variables. The experimental results indicate that the optimum condition of extraction which yield of oleoresin of 11.026% was found at ratio of ginger to ethanol (X1) of 1:4.68 gr.ml-1, extraction temperature (X2) of 420 OC, and extraction duration (X3) of 79 minutes.Keywords: extraction, response surface method, ginger oleoresin, ultrasonic